2020
DOI: 10.1155/2020/8691534
|View full text |Cite
|
Sign up to set email alerts
|

Sema4D Aggravated LPS-Induced Injury via Activation of the MAPK Signaling Pathway in ATDC5 Chondrocytes

Abstract: Osteoarthritis (OA) is the most common chronic degenerative joint disease, and it remains the main cause of chronic disability in elderly individuals. Sema4D (semaphorin 4D) is involved in the immune system and related to bone injury, osteoporosis, osteoblast differentiation, and rheumatoid arthritis. However, the role of Sema4D in OA remains unclear. Hence, the LPS-stimulated chondrocyte cell injury model was constructed in this study to investigate the role of Sema4D in OA development. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
1
9
1
Order By: Relevance
“…At present, abnormal angiogenesis in the subchondral bone leads to invasion of vasculature into the osteochondral junction is a hallmark of human osteoarthritis [46]. Type H 7 BioMed Research International vessels, characterized by high expression of endothelial markers CD31 and Emcn (CD31 hi Emcn hi ), produce a unique microenvironment to maintain perivascular bone progenitor cells and to link angiogenesis to bone progenitor cells [46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, abnormal angiogenesis in the subchondral bone leads to invasion of vasculature into the osteochondral junction is a hallmark of human osteoarthritis [46]. Type H 7 BioMed Research International vessels, characterized by high expression of endothelial markers CD31 and Emcn (CD31 hi Emcn hi ), produce a unique microenvironment to maintain perivascular bone progenitor cells and to link angiogenesis to bone progenitor cells [46].…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly agreed that the activated ERK pathway of MSCs could obviously promote osteogenic differentiation [ 45 ]. In addition, it has been reported that inhibition of the MAPK signaling pathway can effectively protect chondrocytes from damage caused by factors such as Sema4D, which indicate that the MAPK signaling pathway may play an important role in OA [ 46 ]. In the present study, we found out that SDF-1 could obviously activate the ERK signaling which may indicate that SDF-1 may have promoted BMSC migration and osteogenic differentiation through the ERK signal pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a previous study indicated that DUSP4 silencing in diabetes enhanced the activity of the p38/JNK signaling pathway ( 27 ). Additionally, simultaneously activating the MAPK signaling pathway aggravated LPS-induced chondrocyte injury ( 28 ). Ham et al ( 25 ) revealed an association between LPS, DUSPs and ERK1/2 in microglia cells, and highlighted that LPS induced ERK1/2 phosphorylation, thereby regulating the expression of DUSP4 and 6.…”
Section: Discussionmentioning
confidence: 99%
“…By binding to different receptors, sSema4D exhibits different effects on the inflammatory phenotype in different types of cells. For instance, the Sema4D-plexin B1 axis promoted the inflammation of chondrocytes [ 15 ], whereas the Sema4D-plexin B2 axis contributed to the keratinocyte's inflammation [ 16 ]. Interestingly, studies have shown that both plexin B1 and plexin B2 are expressed on the surface of human ECs [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%